2012
DOI: 10.1038/emboj.2012.85
|View full text |Cite
|
Sign up to set email alerts
|

40S subunit dissociation and proteasome-dependent RNA degradation in nonfunctional 25S rRNA decay

Abstract: Eukaryotic cells have quality control systems that eliminate nonfunctional rRNAs with deleterious mutations (nonfunctional rRNA decay, NRD). We have previously reported that 25S NRD requires an E3 ubiquitin ligase complex, which is involved in ribosomal ubiquitination. However, the degradation process of nonfunctional ribosomes has remained unknown. Here, using genetic screening, we identified two ubiquitin-binding complexes, the Cdc48-Npl4-Ufd1 complex (Cdc48 complex) and the proteasome, as the factors involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 51 publications
3
59
0
Order By: Relevance
“…Finally, Cdc48 was implicated in the degradation of nonfunctional 60S subunits (25S NRD for nonfunctional rRNA decay) by promoting the dissociation of stalled 80S, thus allowing the recruitment of the proteasome to stalled 60S to perform ribosomal proteins proteolysis (29). These results are consistent with the hypothesis that after dissociation of stalled ribosomes, the 60S particles are not recycled to perform new rounds or translation but targeted for proteasomal degradation, together with the aberrant nascent peptide.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, Cdc48 was implicated in the degradation of nonfunctional 60S subunits (25S NRD for nonfunctional rRNA decay) by promoting the dissociation of stalled 80S, thus allowing the recruitment of the proteasome to stalled 60S to perform ribosomal proteins proteolysis (29). These results are consistent with the hypothesis that after dissociation of stalled ribosomes, the 60S particles are not recycled to perform new rounds or translation but targeted for proteasomal degradation, together with the aberrant nascent peptide.…”
Section: Discussionsupporting
confidence: 80%
“…Ohno and colleagues recently discovered that this process is mediated by Cdc48 and the proteasome (Fujii et al, 2012). They showed that ribosomes with defective 25S rRNA in the 60S subunit are selectively ubiquitylated by a ubiquitin ligase complex containing Mms1 and Rtt101.…”
Section: Box 2 Clinical Syndromes Associated With Vcp Mutationsmentioning
confidence: 99%
“…They showed that ribosomes with defective 25S rRNA in the 60S subunit are selectively ubiquitylated by a ubiquitin ligase complex containing Mms1 and Rtt101. Subsequently, the Cdc48-Ufd1-Npl4 cofactor complex separates the 60S subunit from the ribosome and facilitates the degradation of ubiquitylated ribosomal proteins by the proteasome (Fujii et al, 2012). It is tempting to speculate that Cdc48 does this by disassembling the individual components of the 60S subunit.…”
Section: Box 2 Clinical Syndromes Associated With Vcp Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These diverse functions of Cdc48/VCP/p97 are mediated by specific adaptors. The best known is the Npl4-Ufd1 complex that is used for Cdc48/VCP/p97 to extract misfolded protein substrates from the ER (Wolf and Stolz, 2012) and to dissociate nonfunctional 60S ribosome subunits for proteasomal degradation (Fujii et al, 2012). Cdc48-Npl4-Ufd1 also remodels chromatin-binding proteins for DNA damage repair (Acs et al, 2011) and promotes turnover of RNA polymerase II upon UV irradiation (Verma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%